Association between somatic cell count early in the first lactation and the lifetime milk yield of cows in Irish dairy herds - Archer, Simon C.; Mc Coy, Finola; Wapenaar, Wendela; Green, Martin J. (American Dairy Science Association, 2013)
Change in lifetime milk yield is an important component of the cost of diseases in dairy cows. Knowledge of the likelihood and scale of potential savings through disease prevention measures is important to evaluate how much expenditure on control measures is rational. The aim of this study was to assess the association between somatic cell count (SCC) at 5 to 30 d in milk during parity 1 (SCC1), and lifetime milk yield for cows in Irish dairy herds. The data set studied included records from 53,652 cows in 5,922 Irish herds. This was split into 2 samples of 2,500 and 3,422 herds at random. Linear models with lifetime milk yield and first-lactation milk yield as the outcomes and random effects to account for variation between herds were fitted to the data for the first sample of herds; data for the second sample were used for cross-validation. The models were developed in a Bayesian framework to include all uncertainty in posterior predictions and parameters were estimated from 10,000 Markov chain Monte Carlo simulations. The final model was a good fit to the data and appeared generalizable to other Irish herds. A unit increase in the natural logarithm of SCC1 was associated with a median decrease in lifetime milk yield of 864kg, and a median decrease in first-lactation milk yield of 105kg. To clarify the meaning of the results in context, microsimulation was used to model the trajectory of individual cows, and evaluate the expected outcomes for particular changes in the herd-level prevalence of cows with SCC1 ≥400,000cells/mL. Differences in mean lifetime milk yield associated with these changes were multiplied by an estimated gross margin for each cow to give the potential difference in milk revenue. Results were presented as probabilities of savings; for example, a 75% probability of savings of at least€97 or€115/heifer calved into the herd existed if the prevalence of cows with SCC1 ≥400,000cells/mL was reduced from ≥20 to <10 or <5%, respectively, and at least€71/heifer calved into the herd if the prevalence of cows with SCC1 ≥400,000cells/mL was reduced from ≥10 to <5%. The results indicate large differences in lifetime milk yield, depending on SCC early in the first lactation and the findings can be used to assess where specific interventions to control heifer mastitis prepartum are likely to be cost effective.